STRATEGI PENGELOLAAN KELAS DALAM MENCIPTAKAN SUASANA BELAJAR YANG KONDUSIF - Oktaviani, Trianur; Alani, Nabella (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of classroom learning implementation. However, in practice, teachers are often faced with various classroom conditions and dynamics that do not always align with expectations. The gap between ideal conditions and reality frequently becomes an obstacle in optimizing the learning process. Therefore, to minimize various problems that arise in the classroom, teachers need to possess skills in implementing effective classroom management strategies. A conducive classroom environment is essential to support learning services for students. Without such an environment, teachers may encounter difficulties in managing the learning process, such as disruptive student behavior, low learning motivation, peer disturbances, and physical classroom issues, including unclean, cramped, unpleasant, and poorly organized spaces. This highlights that the role of the teacher as a classroom manager is not limited to preparing instructional materials and evaluating learning outcomes, but also includes efforts to develop, create, maintain, and improve classroom systems and organization so that students feel comfortable and engaged. A well-managed classroom environment has a significant influence on students' ability to concentrate and absorb learning materials.